The Effect of Job Satisfaction and Organizational Justice on Organizational Citizenship Behavior with Organization Commitment as The Moderator - Fauzi Mihdar (International Conference On Law, Business and Governance (ICon-LBG), 2013)
This study was conducted to determine the influence of job satisfaction and organizational justice onofficer’s organizational citizenship behavior at Regional Office of the Directorate General of Taxes ofBengkulu and Lampung with organizational commitment as moderator. The study sample of 158 officerswas taken by simple random sampling technique. The research data were obtained by using scale methodsand were analyzed by Structural Equation Modeling (SEM). The research results showed: the empiricalmodels influence job satisfaction and organizational justice on organizational citizenship behavior (OCB)with the organizational commitment as moderator which fits with the theoritical model, job satisfactiondirectly has impact on organizational citizenship behavior, organizational justice has a direct impact onorganizational citizenship behavior, organizational commitment has a direct impact on organizationalcitizenship behavior, job satisfaction has impact on organizational citizenship behavior throughorganizational commitment as a moderator, and organizational justice does not have impact onorganizational citizenship behavior through organizational commitment as moderator.